2023
DOI: 10.1038/s41598-023-32257-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite formulation for a sustained release of free drug and drug-loaded responsive nanoparticles: an approach for a local therapy of glioblastoma multiforme

Abstract: Malignant gliomas are a type of primary brain tumour that originates in glial cells. Among them, glioblastoma multiforme (GBM) is the most common and the most aggressive brain tumour in adults, classified as grade IV by the World Health Organization. The standard care for GBM, known as the Stupp protocol includes surgical resection followed by oral chemotherapy with temozolomide (TMZ). This treatment option provides a median survival prognosis of only 16–18 months to patients mainly due to tumour recurrence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The results indicated that glioma tissue exhibited a higher accumulation of LTF than normal brain tissue, implying a potential targeting effect of LTF on the tumor cells. These ndings can be correlated with the immunohistochemistry data, demonstrating that an increased accumulation of LTF nanoparticles in glioma tissue could lead to a higher TMZ concentration, potentially causing a reduction in tumor cell proliferation and thus inhibiting glioma progression [20].…”
Section: Biodistribution and Immunohistochemistrymentioning
confidence: 54%
“…The results indicated that glioma tissue exhibited a higher accumulation of LTF than normal brain tissue, implying a potential targeting effect of LTF on the tumor cells. These ndings can be correlated with the immunohistochemistry data, demonstrating that an increased accumulation of LTF nanoparticles in glioma tissue could lead to a higher TMZ concentration, potentially causing a reduction in tumor cell proliferation and thus inhibiting glioma progression [20].…”
Section: Biodistribution and Immunohistochemistrymentioning
confidence: 54%
“…The findings indicated that glioma tissue exhibited a higher accumulation of LTF than normal brain tissue, implying a potential targeting effect of LTF on the tumor. We can relate the effect of a higher accumulation of LTF nanoparticles in glioma tissue with the immunohistochemistry data, which shows that more TMZ accumulation can cause reduced tumor cell proliferation and thus inhibit glioma progression [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the customization of different nanoparticles (Idlas et al, 2023) and the loading of various molecules (Lin et al, 2023) allow for unlimited potential therapeutic combinations. In some cases, nanoparticles loaded with chemotherapeutics are dispersed into gel matrices (Gu et al, 2022), which function as a shelter to reduce molecule degradation and unwanted cytotoxicity (Erthal et al, 2023). New formulations for in situ delivery aim at optimizing the effects of first-generation anti-glioblastoma agents such as carmustine and temozolomide, either alone or in combination, to maximize their curative effects, for example overcoming the resistance to TMZ using the O 6 alkylguanine DNA alkyltransferase inhibitor, dialdehyde O 6 benzylguanine (DABG), tested in xenograft (Chu et al, 2023) or intracranially delivered, minimizing peripheral toxicity (Chen et al, 2022;Iturrioz-Rodríguez et al, 2023).…”
Section: In Situ Delivery Of Treatmentmentioning
confidence: 99%